Is there a link between financial literacy and financial behaviour? - Kwame Mireku; Francis Appiah; Joseph Akadeagre Agana (Cogent Economics & Finance, 2023)
In this paper, we are motivated by the growing complexity of financial service products amidst an unending wave of Ponzi schemes as well as the low levels of financial literacy reported by prior studies. Particularly, while the extant literature has focused on various determinants of financial literacy, limited insights exist on the implications of financial literacy on financial behaviour. Consequently, we focus our empirical test on identifying the link between financial literacy and financial behaviour. We formulated our hypotheses from the family resource management theory which postulates that individual behaviour is a function of their knowledge. Thus, relative to financial literacy and financial behaviour, we argue that financially literate individuals are more likely to exhibit sound financial behaviour than those who are financially illiterate. We tested our hypothesis by using the logistic regression technique on a cross-sectional sample of 3,932 students pursuing various undergraduate and postgraduate programs in Ghanaian public and private universities. Notably, we selected our respondents from six (6) public and six (6) private universities. Consistent with our theoretical predictions, our results show that financially literate students are more likely to exhibit sound financial behaviour. Specifically, the results demonstrate that financial literacy is a major input for financial behaviour. Additionally, we observe that variables such as family characteristics particularly the father's educational background, and discussion of financial matters at home are significant predictors of sound financial behaviour. Generally, our results have implications for various stakeholders including governments, academic institutions, and families.
Keywords: 330; financial behaviour; financial literacy; Ghana; Logit